ANALISIS EKUITAS MEREK PRODUK TUPPERWARE DI KELURAHAN BABURA KECAMATAN MEDAN BARU - Perys Laili Khodri Nasution; Khairina Khairina (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
The results of research by the author, it can be concluded that brand awareness for Tupperware including the excellent category in which the brand is well known Tupperware respondents, including elements of the overall perception of quality including good category, brand association element is also included in both categories, and brand loyalty for Tupperware which include both categories / consumers loyal to Tupperware products and overall conclusions Tupperware brand has good equity in the views of respondents.Keywords: Brand Equity, Tupperware Products